Iron pyrite nanocrystals as a sustainable nanozyme for colorimetric detection of ceftriaxone sodium in environmental samples - Seyyed Morteza Seyyed Alavi; Mohammad Amjadi; Jamshid L. Manzoori (Scientific Reports)
Abstract Pyrite nanocrystals (PNCs) is a potential alternative to conventional quantum dots due to their favorable properties such as sustainability, cost-effectiveness, low toxicity and tunable luminescence. In this work, we explored peroxidase-like activity of FeS2 PNCs, synthesized by a simple solvothermal method. Nanozymic properties of PNCs were studied with TMB as a substrate. The reaction mechanism was evaluated by Michaelis-Menten equation and the radical scavengers. Utilizing the great enzyme-mimic activity of PNCs we were developed a sensitive colorimetric sensor for determination of ceftriaxone in the range of 0.5–20 nM, and detection limit was 0.13 nM. On the basis of clear color change in the solution, a simple but sensitive smartphone-based platform in the range 10–40 nM with the detection limit of 7.8 nM was also developed. Applicability of these sensors was studied for analysis of various water samples, demonstrating their great potential for real analytical applications.